Correlations for fire-wind enhancement flow characteristics based on LES simulations - Eftekharian, Esmaeel; Ghodrat, Maryam; He, Yaping; Ong, Robert H.; Kwok, Kenny C.S.; Zhao, Ming (The International journal of heat and fluid flow, 2020)
•Correlations are developed for fire-wind enhancement flow characteristics.•Maximum fire-wind enhancement is correlated with dominant non-dimensional groups.•A correlation is developed for the location of maximum fire-wind enhancement.•A correlation is developed for the decay of enhanced wind velocity.•Wind enhancement plume line is introduced for which a correlation is developed. Unraveling the physics of fire-wind interaction has long been a subject of interest. Among all the physics involved, enhancement of wind by fire deserves great attention due to its potential effects on building structures downstream of the fire source in bushfire attack events. Predominantly, two contributing factors determine the extent to which wind is enhanced by fire: freestream wind velocity and fire intensity. This study employs Large-Eddy Simulation (LES) to fundamentally investigate the combined effects of freestream wind velocity and fire intensity on fire-wind enhancement. An added module was implemented to an open-source transient fire solver in order to analyze the effects of freestream wind velocity and fire intensity based on the analysis of interactions between momentum and fire-induced buoyancy forces. Simulations are performed for parametric combinations of wind velocity and fire intensity. The LES results demonstrate that the normalized maximum wind enhancement increases with a reduction of freestream wind velocity and an increase in fire intensity. The non-dimensional Froude number, Fr, and normalized fire intensity, I*, were employed to quantify the effects of freestream wind velocity and fire intensity, respectively. A correlation was developed to determine the maximum wind enhancement as a function of Fr and I*. The location corresponding to maximum wind enhancement occurs further downstream of the fire source as freestream wind velocity or fire intensity increases. A correlation based on the Fr number and I* was developed for the location at which maximum wind enhancement occurs. Furthermore, the concept of wind enhancement plume line was defined as a line along which the local wind enhancement occurs at a given longitudinal location downstream of the fire source, for which a correlation was also developed. Moreover, a gradual decaying trend is observed in wind enhancement after reaching a peak along the wind enhancement plume line in all simulation scenarios for which a correlation was also developed as a function normalized longitudinal direction.